Librarians, Libraries, and the Scholarship of Teaching and Learning. (September 2014) - Otto, Peter
Abstract : Librarians are continually teaching students and faculty how to identify and access learning resources. They teach during individual reference consultations, through presentations to classes, and through library website content they create. Are librarians well prepared to design and deliver well‐crafted instruction? Academic librarians have plentiful resources for developing their pedagogical knowledge through the activities of the Association of College and Research Libraries (ACRL), whose extensive professional development initiatives to advance effective pedagogy are described. The ACRL's definitions of the components of information literacy skills and instructional competencies, described in the chapter, are relevant and important to all teaching faculty. The chapter discusses some of the benefits and outcomes that can arise from librarians' efforts to build and sustain active collaborations with discipline‐specific teaching faculty. Because the library can be at the center of connections among all of the university's academic units, it is well placed to create and support initiatives that develop cross‐disciplinary pedagogical excellence. Beyond their intentional efforts to make teaching and learning resources available for faculty, academic libraries can participate in campus‐wide programs such as an Institutional Repository or a Center for Teaching and Learning that will promote steady growth in the excellence of the university's teaching and learning.